EFEITO DE TRICHODERMA SPP. SOBRE O CRESCIMENTO MICELIAL DE FUNGOS DO GÊNERO RIZHOCTONIA SOLANI - LIMA, Carlos Eduardo Braga Vieira; NUNES, Tiago Calves; CASANOVA, Evelin Arantes; CELOTO, Mercia Ikarugi Bomfim (ANAIS DO ENIC, 2025)
-